Reproductive coercion in Uttar Pradesh, India: Prevalence and associations with partner violence and reproductive health - Jay G. Silverman; Sabrina C. Boyce; Nabamallika Dehingia; Namratha Rao; Dharmoo Chandurkar; Priya Nanda; Katherine Hay; Yamini Atmavilas; Niranjan Saggurti; Anita Raj (Elsevier, 2019)
Increasing modern contraceptive use and gender equity are major foci of the recently ratified Sustainable Development Goals for 2030 and the Government of India. Coercion and sabotage by husbands and in-laws to inhibit women's access, initiation, continuation, and successful use of modern contraception methods (i.e., reproductive coercion) may contribute to low usage rates and unintended pregnancy in India; however, little is known about the extent of this problem. The current study assesses the prevalence of reproductive coercion, both husband and in-law perpetrated, among a large population-based sample. Data were collected from currently married women of reproductive age (15-49 years; N = 1770) across 49 districts of Uttar Pradesh as part of an evaluation of a broad effort to improve the public health system in the state. Dependent variables included modern contraceptive use in the past 12 months, unintended pregnancy, and pregnancy termination. Independent variables included ever experiencing reproductive coercion (RC) by a current husband or in-laws and lifetime experience of physical and sexual intimate partner violence (IPV) by a current husband. Approximately 1 in 8 (12%) women reported ever experiencing RC from their current husbands or in-laws; 42% of these women reported RC by husbands only, 48% reported RC by in-laws only, and 10% reported RC by both husbands and in-laws. Among women experiencing RC, more than one-third (36%) reported that their most recent pregnancy was unintended; these women had 4 to 5 times greater odds of unintended pregnancy and a more than 5 times decreased likelihood of recent use of modern contraceptives than women not experiencing RC, after accounting for effects of demographics and physical and sexual IPV. Scalable and sustainable interventions in both clinical and community settings are needed to reduce RC, a potentially key factor in effective strategies for improving women's reproductive autonomy and health in India and globally. Keywords: Reproductive coercion, Intimate partner violence, India, Unintended pregnancy, Contraception